Whitehead's Theory of Propositions and its Relevance to Language and Ontology - Elliot, Franklin Robert (My University, 1967)
To set forth and explain Whitehead's theory of propositions and to show how this theory is a repudiation of philosophies based upon (i) substance ontology and (ii) an uncritical use of ordinary language. Chapter I is intended to supply the philosophic bases necessary for an understanding of Whitehead's theory of propositions. Chapter II is a development of the doctrine of propositions with reference to: ontology, the notions of truth and falsity, and of error. The theory of relations and its bearing on the theory of proposi tions is also explained. In conclusion, chapter III is intended to show how 11bitehead's theory of propositions may be used to question the legitimacy of an alleged fact-value dichotomy in current scientific method.
Keywords: Philosophy; Philosophy